PERUBAHAN LABA PERUSAHAAN : ANALISIS RASIO DAN PENGARUHNYA - Kurniawan, Lydia; Budiman, Monika; Mahesa, Bella (Jurnal Riset Ekonomi dan Bisnis Mahasiswa : Brainy, 2025)
Businesses listed on the Indonesia Stock Exchange (IDX) in the food and beverage subsector from 2019 to 2023 will have their liquidity, solvency, and activity ratios examined in this study to determine their impact on profit changes. Using the purposive selection technique, 95 companies were chosen as the study's population, with 18 samples serving as research objects. Panel data regression analysis, classical assumption tests, hypothesis tests (t-test and f-test), and a determination coefficient test were all utilized in the quantitative method based on secondary data analysis that was applied to the following sample utilizing Eviews 12. The study's findings reveal that while the liquidity ratio does not significantly impact profit change, the solvency and activity ratios do. These three ratios stand out when it comes to profit turnover. The combined effect of the liquidity ratio, the solvency ratio, and the activity ratio is a considerable 37.31% impact on profit changes; the remaining portion is impacted by elements that are not part of this study. Distinct from previous studies, this one compares the effects of time and space on three key performance indicators: liquidity ratio (X1), solvency ratio (X2), and activity ratio (X3). The results of the research show that the improvement of the liquidity ratio, along with the preservation of the solvency and activity ratios, can significantly affect the change in the company's profit.